2021
DOI: 10.3390/pathogens10091099
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-Induced Inflammation: Possible Factors Modulating the Risk of Gastric Cancer

Abstract: Chronic inflammation and long-term tissue injury are related to many malignancies, including gastric cancer (GC). Helicobacter pylori (H. pylori), classified as a class I carcinogen, induces chronic superficial gastritis followed by gastric carcinogenesis. Despite a high prevalence of H. pylori infection, only about 1–3% of people infected with this bacterium develop GC worldwide. Furthermore, the development of chronic gastritis in some, but not all, H. pylori-infected subjects remains unexplained. These conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 129 publications
(153 reference statements)
0
21
0
Order By: Relevance
“…Recently, it was reported that Helicobacter pylori infection caused gastric and duodenal inflammation [60]. Meanwhile, studies also have shown that interleukin-8 overexpression and iNOS production could be detected in gastritis models.…”
Section: Anti-inflammatory Mechanism Of Resveratrolmentioning
confidence: 99%
“…Recently, it was reported that Helicobacter pylori infection caused gastric and duodenal inflammation [60]. Meanwhile, studies also have shown that interleukin-8 overexpression and iNOS production could be detected in gastritis models.…”
Section: Anti-inflammatory Mechanism Of Resveratrolmentioning
confidence: 99%
“…All these cells of the immune system are involved in maintaining immune homeostasis in the human body and fighting the developing inflammation or fighting pathogens. Chronic H. pylori infection leads to gastritis, and in some patients, peptic ulcer disease, and in about 1%—gastric cancer [ 17 , 18 ]. The likelihood of developing disease in those infected with these microorganisms is largely determined by the long-term inflammatory response that is associated with the virulence of the strains, genetic predisposition of the host, and environmental cofactors.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Therefore, gastric cancer is an inflammation-associated carcinoma promoted by H pylori infection, characterized by ongoing chronic gastritis, development of gastric atrophy (GA), formation of intestinal metaplasia (IM), and finally, dysplasia and cancer. [4][5][6] Then, a relative consensus advocated that H pylori eradication could improve mucosal inflammation and reduce the incidence rates of gastric cancer. [6][7][8][9][10][11] Thus, on reports, H pylori eradication has shifted from treatment to primary prevention of gastric cancer on reports.…”
Section: Introductionmentioning
confidence: 99%